0
$\begingroup$

Let $F$ be a complex Hilbert space and $\mathcal{B}(F)$ be the algebra of all bounded linear operators on $F$.

For ${\bf A} = (A_1,...,A_d) \in \mathcal{B}(F)^d$, the norm of ${\bf A}$ is given by $$\|{\bf A}\|^2=\sum_{k=1}^d\|A_k\|^2.$$

For ${\bf T}=(T_1,...,T_d) \in \mathcal{B}(F)^d$ and ${\bf S}=(S_1,\cdots,S_m)\in \mathcal{B}(F)^m$, we set $$\mathbf{T}\mathbf{S}:=(T_1S_1,\cdots,T_1S_m,T_2S_1,\cdots,T_2S_m,\cdots,T_dS_1,\cdots,T_dS_m).$$ Let $\mathbf{T}^2=\mathbf{T}\mathbf{T}$ and we define by induction $\mathbf{T}^{n+1}=\mathbf{T}\mathbf{T}^n$ for $n\in \mathbb{N}^*$.

Let $n\in \mathbb{N}^*$ and ${\bf T}=(T_1,...,T_d) \in \mathcal{B}(F)^d$ such that the operators $T_k$ are not necessarily commuting, I claim that $$\|\mathbf{T}^n\|^2=\sum_{g\in \mathbf{G}(n,d)}\|\mathbf{T}_g\|^2\,$$ where $g\in \mathbf{G}(n,d)$ and $\mathbf{T}_g:=\prod_{i=1}^dT_{g(i)}$.

Note that $\mathbf{G}(n,d)$ denotes the set of all functions from $\{1,\cdots,n\}$ into $\{1,\cdots,d\}$.

How to prove that the claim is true?

Note that if the operators $T_k$ are commuting, it can be seen that $$\|\mathbf{T}^n\|^2=\sum_{|\alpha|=n}\frac{n!}{\alpha!}\|\mathbf{T}^{\alpha}\|^2.$$ For $\alpha = (\alpha_1,\cdots,\alpha_d) \in \mathbb{N}^d$, we write $\alpha!: =\alpha_1!\cdots\alpha_d!,\;|\alpha|:=\displaystyle\sum_{j=1}^d|\alpha_j|$ and $\mathbf{T}^\alpha:=T_1^{\alpha_1} \cdots T_d^{\alpha_d}$.

$\endgroup$
  • $\begingroup$ You make a claim. Is your question asking how to prove the claim? If so, why do you believe the claim should be true? $\endgroup$ – Yemon Choi Jan 19 at 12:12
  • $\begingroup$ Because I try with an example, such as d=2, n=3. $\endgroup$ – Schüler Jan 19 at 12:17
  • $\begingroup$ I'm a bit confused; why isn't this true just by definition after expanding out? $\endgroup$ – Dongryul Kim Jan 19 at 19:32
2
+50
$\begingroup$

I believe you meant to write $\mathbf{T}_g:=\prod_{i=1}^n T_{g(i)}$ so maybe a better symbol would be $\mathbf{T}_g^n:=\prod_{i=1}^n T_{g(i)}$.

Now, follwing @DongryulKim's suggestion, we can see why your claim holds by observing how $\mathbf{T}^n$ is formed.

Let us characterize functions $g \in G(n,d)$ by the values they take $g_{i_1, i_2, \dots , i_d} \in G(n,d)$, meaning $g_{i_1, i_2, \dots , i_d}(k) = i_k$ with $k \in {1, 2, \dots , n}$ and $i_k \in {1,2,\dots,d}$.

Clearly, when $N=1$ the components run over all the functions in $G(1,d) = \{g_1, g_2 , \dots, g_d \}$ since

$$\mathbf{T}^1 = (T_1, T_2, \dots , T_d) = \left(T_{g_1(1)}, T_{g_2(1)}, \dots, T_{g_d(1)} \right ) = \left(\mathbf{T}_{g_1}^1, \mathbf{T}_{g_2}^1, \dots, \mathbf{T}_{g_d}^1 \right ) $$

Let us assume now that this also holds for $N=n$, that is $$\mathbf{T}^n = (\mathbf{T}_{g_{1,1,\dots,1}}^n, \dots, \mathbf{T}_{g_{i_1,i_2,\dots,i_n}}^n, \dots , \mathbf{T}_{g_{d,d,\dots,d}}^n)$$

Now, going to $N=n+1$ we have

$$\mathbf{T}^{n+1} = (T_1 \mathbf{T}_{g_{1,1,\dots,1}}^n, \dots ,T_1 \mathbf{T}_{g_{d,d,\dots,d}}^n , T_2 \mathbf{T}_{g_{1,1,\dots,1}}^n, \dots, T_2 \mathbf{T}_{g_{d,d,\dots,d}}^n , \cdots , T_d \mathbf{T}_{g_{1,1,\dots,1}}^n, \dots, T_d \mathbf{T}_{g_{d,d,\dots,d}}^n )$$

It is easy now to see from this arrangement that the first block of components corresponds to terms $\mathbf{T}_g^{n+1}$ for functions $g \in G(n+1,d)$ with $g(1) = 1$ and $g(i) = g'(i-1)$ for any function $g' \in G(n,d)$ and $i>1$. Similarly, the second block corresponds to terms $\mathbf{T}_g^{n+1}$ for functions $g \in G(n+1,d)$ with $g(1) = 2$ and $g(i) = g'(i-1)$ for any function $g' \in G(n,d)$ and $i>1$. Following this all the way to the last block, where $g(1) = d$ we see that we have covered all the functions in G(n+1,d). Thus

$$\mathbf{T}^{n+1} = (\mathbf{T}_{g_{1,1,\dots,1}}^{n+1}, \dots,\mathbf{T}_{g_{i_1,i_2,\dots,i_d}}^{n+1},\dots,\mathbf{T}_{g_{d,d,\dots,d}}^{n+1} )$$

So, in general, we have

$$\mathbf{T}^n = (\mathbf{T}_{g_{1,1,\dots,1}}^n, \dots ,\mathbf{T}_{g_{i_1,i_2,\dots,i_d}}^n,\dots,\mathbf{T}_{g_{d,d,\dots,d}}^n )$$

from which we can get

$$ \|\mathbf{T}^n\|^2=\sum_{(i_1,...,i_n) \in \{1,...,d\}^n}\|\mathbf{T}_{g_{i_1,...,i_n}}^n\|^2 = \sum_{g\in \mathbf{G}(n,d)}\|\mathbf{T}_g^n\|^2 $$

$\endgroup$
  • $\begingroup$ I don't understand why you write an element $g \in G(n,d)$ as $g_{i_1, i_2, \dots , i_d} \in G(n,d)$?Thanks. $\endgroup$ – Schüler Jan 27 at 7:23
  • $\begingroup$ It is just an explanatory way to write the elements of $G(n,d)$ so that we can later range over them in a clearer way. It is just a symbolic way of saying that "$g_{i_1, i_2, \dots , i_d}$ is the function that sends $1$ to $i_1$, $2$ to $i_2$, etc." $\endgroup$ – Sotiris Jan 27 at 9:21

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.